A new mixed approach for modelling and assessing environmental influences to value co-creation in the construction industry. Issue 21 (1st November 2016) - Zhang, Jingxiao; Schmidt, Klaus; Xie, Haiyan; Li, Hui
Abstract : This research studies closely related environmental forces that impact the growth of a company and their respective results of value co-creation in an enterprise (VCCE). With the purpose to coordinate environmental forces and VCCE, this paper presents an innovative mixed model (BP-FA-SD method) using expert grading method, BP neural network, factor analysis and system dynamics. In this BP-FA-SD method, environmental forces are categorised into economic force, cultural force and administrative force. The VCCE value space is mainly divided into social value, symbol value and product value. This research applies an expert grading method to assess the environmental forces of the selected cases, computes the synergy condition using the BP method, and implements the cluster analysis and SD simulation with the FA and SD methods correspondingly. The results of the BP-FA-SD method indicated the positive synchronisation of the development of enterprise forces in the selected construction companies. The findings would help enterprises to find the optimal development paths with synergistic outcomes from the internal and external factors. It further provides a new scheme of the system improvement of the VCCE time-to-performance with the momentum of environmental forces. The research presents a comprehensive instrument for fundamental reconsideration of environmental forces and their influences.